Enhancer deletion and allelic effects define a regulatory molecular mechanism at the VLDLR cholesterol GWAS locus - Davis, James P (Hum Mol Genet, 2019)
Total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) are heritable risk factors for cardiovascular disease, yet the molecular mechanisms underlying the majority of blood lipid-associated genome-wide association studies signals remain elusive. One association signal is located in intron 3 of VLDLR; rs3780181-A is a risk allele associated (P ≤ 2 × 10(−9)) with increased TC and LDL-C. We investigated variants, genes and mechanisms underlying this association signal. We used a functional genetic approach to show that the intronic region spanning rs3780181 exhibited 1.6–7.6-fold enhancer activity in human HepG2 hepatocyte, THP-1 monocyte and Simpson-Golabi-Behmel Syndrome (SGBS) preadipocyte cells and that the rs3780181-A risk allele showed significantly less enhancer activity compared with the G allele, consistent with the direction of an expression quantitative trait locus in liver. In addition, rs3780181 alleles showed differential binding to multiple nuclear proteins, including stronger IRF2 binding to the rs3780181 G allele. We used a CRISPR-cas9 approach to delete 475 and 663 bp of the putative enhancer element in HEK293T kidney cells; compared to expression of mock-edited cell lines, the homozygous enhancer deletion cell lines showed 1.2-fold significantly (P < 0.04) decreased expression of VLDLR, as well as 1.5-fold decreased expression of SMARCA2, located 388 kb away. Together, these results identify an enhancer of VLDLR expression and suggest that altered binding of one or more factors bound to rs3780181 alleles decreases enhancer activity and reduces at least VLDLR expression, leading to increased TC and LDL-C.